STRATEGIES EMPLOYED BY THE HEAD OF THE MEDAN PERJUANGAN SUBDISTRICT OFFICE OF RELIGIOUS AFFAIRS IN GUIDING ENGAGED COUPLES - M Fitra Aulia Habib; Azhar Azhar (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2026)
This study examines the strategies used by the Medan Perjuangan Subdistrict Office of Religious Affairs to guide prospective brides and grooms. It identifies the methods and approaches applied, as well as factors that enable or hinder implementation, with the aim of enhancing couples’ readiness to build families characterized by sakinah, mawaddah, and warahmah. The research uses a qualitative, descriptive design. Data were collected through in-depth interviews, observations, and documentation involving the Head of the KUA, marriage officiants, and prospective couples in the marriage counseling program. Data analysis followed the Miles and Huberman interactive model, including data reduction, presentation, and conclusion drawing. Findings show that the guidance strategy at the KUA of Medan Perjuangan Subdistrict is structured and adaptive, delivered through the Marriage Guidance Program (Bimwin), and integrates religious, legal, health, psychological, and social components. Training methods include lectures, discussions, question-and-answer sessions, mock marriage ceremonies, and individual counseling tailored to participants. Supporting factors include clear regulations, cross-sectoral cooperation, available facilities and infrastructure, and the competence of marriage officiants and instructors. Obstacles include participants’ limited time, varying educational backgrounds, and the perception among some that premarital counseling is merely an administrative formality. Overall, these counseling strategies have positively impacted the mental, emotional, and spiritual readiness of prospective couples and have contributed to strengthening family resilience in urban areas.